Building Brighter Brains: Inclusive Mathematics Learning with Media and Constructivist Strategies to Enhance Focus and Recall - Pandia, Weny Safitri S.; Laudra, Asyanti; Caw, Sonia (Delta-Phi: Jurnal Pendidikan Matematika, 2024)
Particularly in inclusive classrooms, the level of teacher assistance also affects student achievement. The issue encountered in mathematics education is the utilization of a unidirectional learning approach, resulting in a lack of meaningful learning. In the classroom, teachers typically exert control over teaching and learning activities. Mathematics is the sole topic that is studied consistently from kindergarten through college. The objective of this study is to elucidate the significance of employing constructivism-based mathematics learning materials for students in inclusive educational institutions. The research methodology employed is a literature review, namely by curating a collection of publications about the research topic through electronic search engines in reputable journals published over the past decade, specifically from 2013 to 2023. The original search was centred around the keywords "constructivism-based mathematics learning" and "use of constructivism-based mathematics learning media." The search results were then filtered based on "exclusive criteria" and subsequently examined. The study findings indicate that the utilization of media to support a constructivism-based approach in inclusive classrooms significantly impacts the learning of mathematics. The rationale behind employing a media-assisted constructivist method in inclusive classrooms is that it enables pupils to cultivate greater autonomy in resolving mathematics difficulties. This essay will provide a detailed analysis of the additional advantages of incorporating media into mathematics education in inclusive schools, particularly when employing a constructivist instructional method.